Contemporary issues of open data in information systems research: Considerations and recommendations - Link, G; Lumbard, K; Conboy, K; Feldman, M; Feller, J; George, J; Germonprez, M; Goggins, S; Jeske, D; Kiely, G; Schuster, K; Willis, M (Association for Information Systems, 2017)
Researchers, governments, and funding agencies are calling on research disciplines to embrace open data—data that anyone can access and use. They have done so based on the premise that research efforts can draw and generate several benefits from open data because it might provide further insight and enable individuals to replicate and extend current knowledge in different contexts. These potential benefits, coupled with a global push towards open data policies, bring open data into the agenda of research disciplines, which includes information systems (IS). In this paper, we respond to these developments as follows. We outline themes in the ongoing discussion around open data in the IS discipline. The themes fall into two clusters: 1) the motivation for open data includes themes of mandated sharing, benefits to the research process, extending the life of research data, and career impact; and 2) the implementation of open data includes themes of governance, socio-technical system, standards, data quality, and ethical considerations. In this paper, we outline the findings from a pre-ICIS 2016 workshop on the topic of open data. The workshop discussion confirmed themes and identified issues that require attention in terms of the approaches that IS researchers currently use. The IS discipline offers a unique knowledge base, tools, and methods that can advance open data across disciplines. Based on our findings, we provide suggestions on how IS researchers can drive the open data conversation. Further, we provide advice for adopting and establishing procedures and guidelines for archiving, evaluating, and using open data.